Pengembangan Algoflow Untuk Pembelajaran Algoritma Berbasis Problem Based Learning - Cahya Dwi Rahmawati; Ramadhan Cakra Wibawa (CV. SINAR HOWUHOWU, 2026)
Algorithm learning at SMK Negeri 1 Lamongan faces several challeges, including low learning motivation among Grade X Accounting students, a learning process that has not gradually built foundational algorithmic thinking, and limited access to computer laboratories. This study aims to develop AlgoFlow, a web-based learning media with a Problem Based Learning (PBL) approach on flowchart algorithm material, and to assess the media’s feasibility based on expert Evaluation and student responses. This study employed the Research and Developmt (R&D) method using the ADDIE Development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 33 Grade X Accounting 1 students of SMKN 1 Lamongan. Data collection instruments included media expert validation questionnaires, learning expert validation questionnaires, and student response qustionnaires based on the Tehcnology Acceptance Model (TAM). The results showed that AlgoFlow was declared highly feasible based on media expert validation with a percentage of 93,3% and learning expert validation with a percentage of 92,67%, both categorized as “Very Feasible”. The student response Analysis using the TAM model showed that all variables in the “Agree” category, with Perceived Ease of Use (PEOU) at 77,45%, Perceived Usefullnes (PU) at 76,97%, Attitude Toward Using Technology (ATUT) at 78,18%, Behavioral Intention to Use (BITU) at 76,82%, and Actual Technology Use (ATU) at 77,58%. These results indicate that AlgoFlow is feasible and well-accepted by students in flowchart algorithm learning.